HUBUNGAN KONSUMSI LEMAK, SERAT DAN STATUS GIZI DENGAN KADAR KOLESTEROL TOTAL PENDERITA PENYAKIT JANTUNG - Kamsiah, Kamsiah (JURNAL MEDIA KESEHATAN, 2015)
Heart Sickness and Vein (This PJPD) is disease able to be prevented, where 50%death early can be prevented with preventive efforts regarding/ hit change of life style like patterneat. By have to limit fat consumption, multiply fibre consumption and maintain status of gizinormal. Intention of this research that is to know of its amount of fat consumption, status and fibreof gizi with total cholesterol rate patient of heart sickness heart poli of RSUD M. YunusBengkulu.Which is used in research that is Cross Sectional, with intake of sampel in this researchuse Purposive Sampling tekhnik that is intake of sampel conducted by taking responder or patientmatching with determined by criterion researcher. Analyse Univariat use statistical methods, andBivariate analysis use Correlation. Result of research indicate that there is having a meaningwith p =0.005<0.05, variable of is amount of fat consumption and Status of Gizi with total cholesterolrate at heart sickness patient in Poli Heart of RSUD Dr M Yunus Bengkulu, and there nohaving a meaning of variable of asupan fibre with total cholesterol rate with p = 0,527> 0.05 andgot the nature of correlation of negative weak that is - 0,091 with the meaning excelsior consumefibre hence progressively lower total cholesterol rate patient of heart sickness in Poli Heart ofRSUD Dr M Yunus Bengkulu. Patient of heart sickness can limit fat consumption, improving fibreconsumption so that to be total cholesterol earn normal so that patient of heart sickness canapply healthy life pattern.